Preparation and Properties of Silver Nanoparticles by Heat-combined Electrochemical Method - Tuan, Tran Quoc; Hao, Pham Van; Quynh, Luu Manh; Luong, Nguyen Hoang; Hai, Nguyen Hoang (VNU Journal of Science: Mathematics - Physics; Vol 31 No 2, 2015)
Silver nanoparticles colloid has been prepared by heat-combined electrochemical method, which uses simple and low-cost equipment of easy installation and operation, is easily deployed in industrial scale. A silver plate was used as the cathode instead of silver salts to avoid unexpected ions from the salts. The cathode was made from a stainless steel plate. The chemical used as the electrolyte solution is TriSodium Citrate (TSC). Silver nanoparticles made by the above method are spherical, small-sized, its size distribution ranges from 3-12nm, stably dispersing in a non-toxic solution. Bactericidal capacity of silver nanoparticles are tested on 4 types of common bacteria and fungi. The results showed that silver nanoparticles with a concentration of 10 ppm have a good bactericidal capacity against the said bacteria. This result shows that silver nanoparticles made by heat-combined electrochemical method can be used in antibacterial applications. Keywords: Silvernanoparticle, electrolysis, TriSodium Citrate, antibacterial.